Uji Aktivitas Antioksidan Ekstrak Etanol 96% Daun Karamunting (Melastoma malabathricum L.) dengan Metode CUPRAC - Nabila Saputri; Rahmi Muthia; Muhammad Hidayatullah (BORNEO JOURNAL OF PHARMASCIENTECH, 2023)
Free radicals are compounds that can damage cellular structures in the body, including DNA, lipids and proteins. Antioxidants are compounds that can inhibit the oxidation process. Karamunting leaves (Melastoma malabathricum L.) a plant that can be used as a natural antioxidant source. The purpose of this study was to determine the content of secondary metabolites contained in 96% ethanol extract of caramunting leaves and to determine the EC50 value obtained from the antioxidant activity test of caramunting leaf extract tested quantitatively using the CUPRAC (Cupric Ion Reducing Antioxidant Capacity) method. Karamunting leaves (Melastoma malabathricum L.) were extracted using maceration method with 96% ethanol solvent. Testing the antioxidant activity of caramunting leaves using the CUPRAC (Cupric Ion Reducing Antioxidant Capacity) method with a UV-Vis spectrophotometer with quercetin as a comparison. The quercetin test for comparison is with a concentration of 1; 2; 3; 4; 5; ppm and extract samples with a concentration of 25; 50; 75; 100; 125; ppm. In the phytochemical screening test, positive results were obtained for containing antioxidants in the test for alkaloids, phenols, flavonoids, saponins, steroids, tannins. The results of the study showed that the EC50 with quercetin was 3.8059 ppm and the EC50 value of 96% ethanol extract of caramunting leaves (Melastoma malabathricum L.) was 61.6185 ppm. In conclusion, 96% ethanol extract of karamunting leaves is classified as a strong antioxidant activity.